ANALYSIS OF ACCOUNTING TREATMENT OF BIOLOGICAL ASSETS BASED ON PSAK NO. 69 AT LATONANG FARM PAREPARE CITY - Heriana; Abdul Hamid; Musmulyadi (Institut Agama Islam Negeri Parepare, 2024)
This research aims to determine the accounting treatment of biological assets based on PSAK No. 69 at Latonang Farm and to determine the accounting treatment of biological assets at Latonang Farm from a sharia perspective as well as the implications of implementing PSAK No. 69 to the financial statements of Latonang Farm's biological assets. This was done to analyze the suitability of the accounting treatment for Latonang Farm's biological assets with PSAK No. 69. This research uses qualitative methods with a case study approach and field research. The data collection and data processing techniques use observation, interview and documentation methods. The validity test of the data used in this research is the credibility test. Meanwhile, the data analysis techniques used are data reduction, data presentation and drawing conclusions. The research results show that the accounting treatment of biological assets is based on PSAK No. 69 at Latonang Farm is generally in line with the provisions of PSAK No. 69. However, there are differences regarding the measurement of fair value. Latonang Farm does not revaluate the value of biological assets, but instead uses the acquisition price with adjustments at the end of each period. This approach was chosen because of the difficulty of measuring the value of biological assets precisely. This action is permitted in accordance with the provisions of PSAK No. 69 paragraph 30. Apart from that, the accounting treatment of biological assets at Latonang Farm is also in accordance with the sharia perspective, where the principles of honesty, trust and benefit are applied.